Purpose, meaning, and passion (Harvard Business Review Press, 2018)
In an ideal world, our work lives would be completely fulfilling, full of meaning, and intrinsically motivating. So what if you're stuck in a job and your heart isn't in it anymore? Or what if your team is feeling disconnected from your company's mission? This book shows how to use passion as a compass to find the job that's right for you--and to connect with the deeper purpose of your work